Positionality as a Data Point in Race Research - Milner, H. Richard; Singer, John N.; Parks, Laura; Murray, Ira; Lane-Bonds, Dena (Qualitative inquiry, 2025)
Increasingly, journal editors are requesting researchers to include positionality statements in submissions and publications of manuscripts. These statements are a step in the right direction to help consumers of research identify, make sense of, critique, and understand researchers’ roles in race research. However, we stress the need to build positionality framing throughout qualitative research methods, processes, and dissemination. We argue a need for and demonstrate how researchers might construct positionality as a data point for consumers throughout a research process as a form of “me-search” centering race—before, during, and after research.